The Influence of The Characteristics of The Sharia Supervisory Board on The Maqashid Syariah Index in Sharia Commercial Banks - Setianingsih, Ratih; Mai, Muhamad Umar; Muhammad Syaiful Nurasman (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
Abstract: This study aims to analyze the effect of the characteristics of the Sharia Supervisory Board on the Maqashid Syariah Index at Islamic commercial banks in Indonesia for the period 2014-2023. This study uses a quantitative method, descriptive approach, with the sample being the entire population of this study, namely all Islamic commercial banks in Indonesia registered with the OJK during the period 2014-2023, a many of 16 Islamic commercial banks. Hypothesis testing in this study uses panel data regression analysis and Stata 17 as a tool. The results showed that age has a significant positive effect on the Maqashid Syariah Index. In contrast, size, tenure, and proportion of women have a significant negative effect on the Maqashid Syariah Index. Meanwhile, the frequency of meetings has no effect on the Maqashid Syariah Index. Keywords: Islamic Commercial Banks, Sharia Supervisory Board, Maqashid Syariah Index